Upaya Meningkatkan Kinerja dan Kompetensi Guru Pendidikan Agama Katolik di Papua - Donatus Wea (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2021)
The purpose of this study was to determine the effect of recruitment and awareness of vocations as Catholic religious education teachers on teacher performance in schools with competence as an mediation variable. Primary data was collected through questionnaires to 51 Catholic religious education teachers in the archdiocese of Merauke. Five hypotheses were tested by multiple linear regression analysis. The results of the study showed that five hypotheses proved significant. This finding indicates that the highest percentage of variables that influence directly or indirectly on teacher performance in schools is competence. Recruitment and awareness of the special vocation as a Catholic religion teacher also had a positive effect on performance but with a lower percentage. This indicates that competence plays a dominant role in improving the performance of Catholic religious education teacher in schools. These findings also serve as input for school administrators to apply the procedures for recruitment and selection of candidates of Catholic religious education teachers according to what is regulated in the Code of Canon Law 1983.The recruitment process is quite specific, providing enormous opportunities for obtaining Catholic religious education teachers who really aware of the special vocation and have sufficient competence. Existing aspects will affect the performance as a teacher when actively involved in teaching and educating children in school.